The Survival of the Script: Disavowal and the Persistence of the Symbolic Order in The Last One - Oktariza, Dodi; Syofyan, Donny (Krinok:Jurnal Linguistik Budaya, 2025)
This study provides a psychoanalytic exploration of Alexandra Oliva’s novel The Last One (2016), examining the protagonist Zoo’s psychological endurance through a global pandemic. By utilizing a qualitative symptomatic reading of the text, the research investigates how Zoo maintains her equilibrium by adhering to the "Symbolic Order" of a reality television show even as the "Real" foundations of civilization collapse. Central to this analysis is the mechanism of fetishistic disavowal, expressed through the formula "I know very well, but nevertheless," which allows the protagonist to reframe catastrophic evidence—such as corpses and societal decay—as elaborate production "props" and scripted "challenges" (Žižek, 1997; Oliva, 2016).The findings reveal that Zoo’s survival is predicated on an "internalized gaze" and a persistent performance for an imagined audience, illustrating the profound power of mediated narratives over visceral reality (Lacan, 1978). However, the study also identifies the "Abject" as the ultimate point of psychological failure, where maternal anxiety and sensory intimacy finally pierce her symbolic shield (Kristeva, 1982). Ultimately, this article argues that The Last One serves as a haunting allegory for a hyperreal culture, demonstrating that the human psyche may prioritize a constructed "Script" to defer the trauma of the unassimilable Real.